(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
This study aimed to recognize the parent’s attitudes of normal and hearing impaired pupils towards the inclusion of those pupils in first stage of basic learning. The sample consisted of 40 hearing impaired parents and 40 normal pupils’ parents. The researcher applied the descriptive analytic approach. The instrument used is a scale for parents’ attitudes towards inclusion hearing impaired pupils in public schools. Then the data were analyzed using SPSS. The results of the study were: 1- There are statistically significant differences in hearing impaired pupils’ parents and normal pupils’ parents for the sake of hearing impaired pupils’ parents in all scale dimensions. 2- There are no statistically significant differences in normal pupils parents towards inclusion according to the variable of gender in the first and fourth dimensions (general attitude towards inclusion, the effect of inclusion program on normal pupils). However there are statistically significant differences in normal pupils parents towards inclusion in second and third dimensions (the parents’ attitudes of hearing impaired and normal pupils towards inclusion and the effect of inclusion on hearing impaired pupils). 3- There are no statistically significant differences in hearing impaired pupils parents towards inclusion according to the variable of gender. 4- There are no statistically significant differences in hearing impaired pupils parents and normal pupils parents towards inclusion according to the variable of educational level.